Pengaruh Penerapan Pengendalian Internal, Kesesuaian Kompensasi, Dan Kesadaran Anti Fraud Terhadap Pencegahan Fraud - Laelatul Isnaeni; Novi Akhsani (CV. ITTC INDONESIA, 2025)
This research aims to analyze the influence of internal control, suitability of compensation and anti-fraud awareness. This research was conducted by analyzing fraud prevention at PT. Sugih Boga Nusantara. The sample used in this research was 37 people using a saturated sampling technique. The data used in this research is primary data in the form of distributing questionnaires to employees who work as Shop Heads, Admins and Cashiers at PT Sugih Boga Nusantara restaurant branches which has been used as a research sample. The variables used in this research are Internal Control (X1) as the first independent variable, Compensation Suitability (X2) as the second independent variable, and Anti-Fraud Awareness (X3) as the third independent variable and Fraud Prevention (Y) as the dependent variable. The multiple regression method was used as the research methodology in this study. Analysis of research results using SPSS 20 software. Based on the research results, it can be concluded that internal control has a negative and significant effect on fraud prevention, anti-fraud awareness has a positive and significant effect on fraud prevention, while compensation suitability has no effect on fraud prevention.